RECONCILING CONSTITUTIONAL RULES AND INTERNATIONAL LAWS: A DOCTRINAL STUDY ON THE INNOVATIVE ROLE OF CONSTITUTIONAL RECONCILIATION IN IRAQ AND EGYPT (UUM Journal of Legal Studies, 2024)
This research employs a doctrinal study methodology to investigate the conflict between constitutional rules and international rules,emphasizing the emerging jurisdiction of constitutional reconciliation. Through case studies in Iraq and Egypt, the study seeks to identify crucial criteria for addressing conflicts within the legal framework. A systematic analysis of legal principles, precedents, and existing literature provides a comprehensive understanding of the intricate dynamics involved in resolving conflicts between constitutional provisions and international rules. The research delves into nuanced conflicts arising in the absence of specified applicable laws in constitutional provisions, particularly where international treaties intersect with or deviate from domestic legislation. It aims to elucidate the mechanisms employed by domestic judges, utilizing constitutional reconciliation, when confronted with conflicts between provisions in domestic law and those in treaties. The central inquiry focuses on determining the prevailing legal framework—domestic law or international treaty—with constitutional reconciliation emerging as a novel jurisdiction to rectify such conflicts. In addressing the conflict between constitutional rules and international rules, the study aims to develop an effective resolution mechanism, underscoring the importance of constitutional reconciliation to harmonize international law with domestic legal frameworks. Grounded in a comprehensive understanding of international law regarding the authority of constitutional judges, the analytical method is complemented by the doctrinal study. By integrating the jurisdiction of constitutional reconciliation into the methodology and employing Iraq and Egypt as case studies, this research contributes to a nuanced comprehension of how constitutional judges can navigate and harmonize the interplay between domestic and international legal frameworks. This approach ensures the preservation of both sets of rules without compromising either, advancing our understanding of the complexities involved in addressing conflicts between constitutional and international rules through the innovative lens of constitutional reconciliation.